Targetting an LncRNA P5848-ENO1 axis inhibits tumor growth in hepatocellular carcinoma. Issue 11 (15th November 2019) - Zhu, Xidan; Yu, Hui; Li, Baolin; Quan, Jing; Zeng, Zhangrui; Li, Guangrong; Liu, Jinbo
Abstract: Hepatocellular carcinoma (HCC) has a high recurrence rate and poor clinical outcome after currently used therapies, including radiofrequency ablation. To explore the possible mechanisms for the relapse of HCC, in the present study we focussed on long non-coding RNA (LncRNA), which has been reported to be involved in tumorigenesis. We identified an LncRNA P5848, whose expression level was up-regulated in tumor samples from HCC patients after radiofrequency ablation. As such, we speculated that LncRNA P5848 may play a role in tumor growth. Here we showed that LncRNA P5848, whose up-regulation can lead to HCC cancer cell proliferation and migration. In vitro and in vivo overexpression of LncRNA P5848 promoted cell growth, cell survival, and cell invasion, whereas LncRNA P5848 depletion exerts opposite effects. Mechanistically, we have found that ENO1 was the target of LncRNA P5848. LncRNA P5848 up-regulated the gene and protein expression level of ENO1, promoting tumor growth and cell survival. However, siRNA-mediated knockdown of ENO1 counteracted the effects of LncRNA P5848 on cancer cell growth, cell survival, and migration. Taken together, LncRNA P5848 promotes HCC development by up-regulating ENO1, indicating that LncRNA P5848-ENO1 axis is a potential therapeutic target for the treatment of HCC.